2019
DOI: 10.1061/(asce)co.1943-7862.0001674
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Stakeholders in Off-Site Manufacturing: A Literature Review

Abstract: Off-site manufacturing (OSM) has been attracted much attention in the construction industry. OSM stakeholders are crucial and have a distinguished nature in their management. However, an in-depth understanding of OSM stakeholders and their coordination are still lacking. The paper intends to (a) provide a critical review and analysis of OSM stakeholders based on prior studies, and (b) develop a research framework for their future improvement and practice. The qualitative content analysis was adopted to analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 135 publications
1
74
0
Order By: Relevance
“…Much of the improved safety is due to the reduced environmental hazards in off-site manufacturing [2]. The safe and less hazardous environment also enhances productivity and the quality of the products [54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the improved safety is due to the reduced environmental hazards in off-site manufacturing [2]. The safe and less hazardous environment also enhances productivity and the quality of the products [54].…”
Section: Discussionmentioning
confidence: 99%
“…Required Accurate Planning [46]; [47]; [48] Transportation Challenges [46]; [49]; [50] Negative Public and Expert Perception [51]; [52] Establishment Cost and Cost Due to Complexity [4]; [19]; [10]; [51]; [53] Excessive Coordination Needed [54]; [55] Require Accurate Planning: O'Connor et al [46] indicated that the project planning process of modular construction differs approximately 37% from the project planning of conventional construction. The differences might include the overall planning, cost estimation, scoping, design, etc.…”
Section: Limitation Source(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, BIM as a real-time information sharing platform makes a significant contribution to multi-disciplinary collaboration and coordination in conventional construction [81,82]. In contrast to conventional construction, modular construction is a typical process-intensive approach, with a relatively interdependent supply chain that needs a mature solution for coordination and communication among all stakeholders throughout the entire life cycle [83]. As a consequence, BIM has great potential to act as a communication platform during modular construction that is a possible solution to C9, "lack of coordination and communication", the foremost constraints from the questionnaire.…”
Section: Building Information Modelling (Bim)mentioning
confidence: 99%
“…Prefabricated buildings is also called modular buildings [ 4 ]. Compared with traditional cast-in-situ concrete building, it can minimize construction time, save construction water and reduce environmental pollution [ 5 8 ]. In addition, the United Nations Environment Program (UNEP) points out that prefabricated buildings can also reduce building energy consumption and greenhouse gas emissions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%